PELANGGARAN PRINSIP KERJASAMA STUDI KASUS PADA WACANA KAIWA NICHIJOU SEIKATSU NI MIRU NI NIHON NO BUNKA DARI READING TUTOR HOMEPAGE - Silfani Silfani; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Grice‟s Cooperative Principle is an assumed basic concept in pragmatics, yet its interpretation is often problematic. The use of the word „cooperative‟ seems to lead to a confusion between Grice‟s technical notion and the general meaning associated with the lexeme cooperation, leading to what we term „cooperation drift‟. We argue that these misinterpretations stem, in part, from the relocation of the Cooperative Principle from philosophy to linguistics. In order to access a meaning that is more representative of Grice‟s view, it is necessary to see the writings on the Cooperative Principle and Conversasional Implicatures in the context of George Yule‟s work as a whole. A close study of Grice‟s writings shows the concept of cooperation to be peripheral to his thought: the recurring issues are the distinction between sentence-meaning and speaker-meaning, the idea of systematicity in language, and the centrality of rationality to human action. The research discussed about Cooperative Principle‟s offense in kaiwa (conversation) in Reading Tutor Homepage. From 20 data, there are 5 offense of maxim of quantity, 7 data by maxim of quality, 2 data by maxim of relevance, and 6 data by maxim of manner.Keywords : Cooperative Principle, Meaning or Purpose, Conversasional Implicatures